(3eUGObI GdENhGfs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3HGH CUfGa GdENhGf ; MOKfG eMeO Hf Ydj GdYWGQ Yf CMeO Hf eMeO Hf YjSi Yf HYV CUMGHfG Yf jhfS Hf YHO GdQMef Yf CHj LYaQ Ydjg GdSdGe bGd bGe Edi CejQ GdeDefjf Ydjg GdSdGe (B...s
(3BNQgG (B:s
.. (3Yf GdLGQhO Yf CHj YHO Gddg Ydjg GdSdGe bGd jCJj Ydi GdfGS ReGf djS ajg TjA CYR ef CN Gh cSH OQge ef MdGd (B.(3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \274s
(3EjVGM Gdecfhf (B4\491s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs